Las instituciones en vilo. Derecho y democracia en América Latina (2008)
This work constitutes a proposal of analysis of the relation between law and democracy in the Latin American context. Enquire about the role the law plays in the democratization on a regional level and the rule of the law in specific political circumstances, making significant inquisitions in the topic and dealing –starting at a revision of the pertinent theory– with empiric cases that exemplifies the identified problems to make some initial conclusions regarding the matter.